Implementation of Government Regulation Number 20 Year 2021 Concerning Control of Study Abandoned Area and Land on HGB Land Indicted as Abandoned Land in Madiun City - Brilliant Setyo Pambudi; Suhariningsih Suhariningsih; Fathul Laila (Budapest International Research and Critics University, 2022)
This abstract is entitled